Oligomeric state of the ZIKV E protein defines protective immune responses - Stefan W. Metz (Nature Portfolio, 2019)
Many human antibodies that neutralize Zika virus recognize quaternary epitopes on the envelope (E) protein. Here, Metz et al. engineer stable recombinant homodimers of Zika virus E protein and show that it induces neutralizing antibodies in mice that recognize similar epitopes as human antibodies from Zika infected people.